Exosomes Derived From Human Urine-Derived Stem Cells Overexpressing miR-140-5p Alleviate Knee Osteoarthritis Through Downregulation of VEGFA in a Rat Model - Liu, Yuan; Zeng, Yi; Si, Hai-Bo; Tang, Li; Xie, Hui-Qi; Shen, Bin (The American journal of sports medicine, 2022)
Knee osteoarthritis (KOA) is one of the most common chronic musculoskeletal disorders worldwide, for which exosomes derived from stem cells may provide an effective treatment. To assess the effect of exosomes derived from human urine-derived stem cells (hUSCs) overexpressing miR-140-5p (miR means microRNA) on KOA in an in vitro interleukin 1β (IL-1β)-induced osteoarthritis (OA) model and an in vivo rat KOA model. Controlled laboratory study. Exosomes derived from hUSCs (hUSC-Exos) were isolated and validated. The hUSCs were transfected with miR-140s using lentivirus, and exosomes secreted from such cells (hUSC-140-Exos) were collected. The roles of hUSC-Exos and hUSC-140-Exos in protecting chondrocytes against IL-1β treatment were compared by analyzing the proliferation, migration, apoptosis, and secretion of extracellular matrix (ECM) in chondrocytes. After vascular endothelial growth factor A (VEGFA) was identified as a target of miR-140, the mechanism by which VEGFA can mediate the beneficial effect of miR-140 on OA was investigated using small interfering RNA transfection or chemical drugs. The expression of VEGFA in cartilage and synovial fluid from patients with KOA was measured and compared with that of healthy controls. Surgery for anterior cruciate ligament transection and destabilization of the medial meniscus were performed on the knee joints of Sprague-Dawley rats to establish an animal model of OA, and intra-articular (IA) injection of hUSC-Exos or hUSC-140-Exos was conducted at 4 to 8 weeks after the surgery. Cartilage regeneration and subchondral bone remodeling were evaluated through histological staining and micro-computed tomography analysis. Proliferation and migration ability were enhanced and apoptosis was inhibited in chondrocytes treated with IL-1β via hUSC-Exos, with the side effect of decreased ECM secretion. hUSC-140-Exos not only retained the advantages of hUSC-Exos but also increased the secretion of ECM by targeting VEGFA, including collagen II and aggrecan. Increased expression of VEGFA during the progression of KOA was also confirmed in cartilage and synovial fluid samples obtained from patients with OA. In the rat OA model, IA injection of hUSC-140-Exos enhanced cartilage regeneration and subchondral bone remodeling. Our results demonstrated the superiority of hUSC-Exos overexpressing miR-140-5p for treating OA compared with the hUSC-Exos. The effect of hUSC-140-Exos for suppressing the progression of KOA is in part mediated by VEGFA. Exosomes derived from stem cells may provide a promising treatment for KOA, and our study can advance the related basic research.